Navigating smoking cessation in healthcare: a pilot study of the SMOKE AKAT questionnaire among family medicine residents - Petričušić, Iva; Marelić, Marko; Ćenan, Ljiljana; Brborović, Hana; Brborović, Ognjen (Frontiers in Public Health, 2025)
IntroductionFamily medicine doctors play a crucial role in smoking cessation efforts but often lack adequate training and skills in this area. This study aimed to assess attitudes, knowledge, and behaviors regarding smoking cessation among family medicine residents using a newly developed instrument.MethodsA novel 29-item questionnaire called “Attitudes and Knowledge Assessing Tool on Smoking Cessation Methods” (SMOKE AKAT) was developed and administered online to 161 family medicine residents at the University of Zagreb. This cross-sectional survey assessed knowledge about smoking-related health risks, cessation methods, and harm reduction approaches, as well as attitudes and behaviors related to smoking cessation counseling. Descriptive statistics were used to analyze the responses.Results93 residents completed the survey (57.76% response rate). Key findings include: 91.4% had never received formal education on smoking cessation methods; 62.4% incorrectly believed nicotine causes cancer; 84.9% incorrectly classified e-cigarettes as nicotine replacement therapy; only 57% correctly identified the definition of harm reduction; 51.6% reported spending 2–5 min on cessation counseling per patient visit; and 84.9% believed family doctors should be responsible for implementing smoking cessation interventions.ConclusionIn light of the European Commission’s agenda to make the EU smoke-free by 2040, where healthcare professionals play an increasingly crucial role this study revealed significant knowledge gaps and misconceptions about smoking cessation among family medicine residents. Many lack formal training but express interest in further education. There is a need to enhance smoking cessation curricula in family medicine training programs, focusing on evidence-based cessation methods, pharmacotherapy options, and harm reduction approaches. Improving residents’ knowledge and skills in this area could lead to more effective smoking cessation interventions in primary care settings. The SMOKE AKAT questionnaire addresses a critical gap in the current healthcare research landscape by providing an assessment tool to identify knowledge deficiencies, attitudinal barriers, and practice gaps among family medicine physicians in smoking cessation counseling and enables targeted educational interventions to correct specific deficiencies that might otherwise remain undetected in standard medical education assessments.